Design selection of experimental test rig for static thrust on micro size propeller using Pugh method / Noor Iswadi Ismail ... [et al.] - Ismail, Noor Iswadi; Amir, Muhammad Amirul Hakim; Basri, M. Hisyam; Sharudin, Hazim; Che Mat, Sharzali; Ab Hamid Pahmi, Muhammad Arif; Husin, Azmi; Othman, Rozaini; Kassim, Umar (Universiti Teknologi MARA Cawangan Pulau Pinang, 2024)
This paper aims to propose a simple, straightforward, yet robust test rig design to measure the static thrust magnitude for small propellers. Although there were advanced tools like multi-axis force or torque sensors, sophisticated equipment and complex mechanisms were required to capture the accurate thrust magnitude. Therefore, providing simple and effective test rig design for small-sized propellers is quite challenging. In this work, Pugh matrix analysis was used to evaluate three new designs of Propeller Thrust Measurement Rig (PMTR) and compare the designs against a benchmark model. The evaluation covered important design criteria during test operation, such as measurement accuracy, stability, ease of development, assembly, maintenance, versatility, electronic integration, airflow interference, adaptability for tilt angle studies, and resemblance to multicopter flight conditions. The results reveal that the PMTR-1 design scored the highest in the analysis and emerged as the most suitable candidate among the proposed designs. It showed potential superior performance in stability, ease of development and assembly, versatility, simplicity, airflow management, and adaptability for future studies. PMTR-3 demonstrated some potential but needs more enhancement in electronic integration and structural development. However, PMTR-2 faces significant potential challenges in providing stability, versatility, electronic integration, and adaptability for effective and safe operations.